Costa Rica : Staff Report for the Second Review Under the Stand-By Arrangement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Costa Rica. (IMF Staff Country Reports; Country Report, 2010)
This paper discusses key findings of the IMF staff report for Costa Rica for the Second Review Under the Stand-By Arrangement (SBA). Performance under the SBA has remained strong. All quantitative performance criteria for end-September were met, most with considerable margins. The authorities have continued to treat the SBA as precautionary. The outlook for a gradual recovery amid domestic and external stability remains the central scenario. Program risks have declined further and now appear broadly balanced. The main threat to the growth outlook is the possibility of a slower-than-expected global recovery.